Project-Based Learning Model to Promote Preservice Science Teachers’ Metacognitive Skills - Wisarut Payoungkiattikun; Angkhan Intanin; Tawan Thongsuk; Chulida Hemtasin (Journal of Educational Issues, 2024)
The purpose of this study was to build a project-based learning (PjBL) model using Susan A. Ambrose et al. cycle’s metacognition conceptual framework. The PjBL approach was created to improve the preservice science teacher’s metacognitive skills. Methods: To modify the PjBL strategy, this study began with a basic review of PjBL and metacognitive skills backgrounds. Results: A panel of experts used the item-objective congruence index (IOC) at five distinct levels to evaluate the validity of the PjBL model. The PjBL model’s appropriateness rating was calculated as 4.56, which showed that it was very suited.